Doping controls and the 'Mature Minor' elite athlete: towards clarification?. Issue 1 (2nd January 2020) - Kleiderman, Erika; Thompson, Rachel; Borry, Pascal; Boily, Audrey; Knoppers, Bartha Maria
ABSTRACT: Doping control is an integral part of participation in sport. It aims to protect the health of athletes and to preserve the integrity and intrinsic values associated with elite sport. The World-Anti-Doping Code applies to all participating athletes, irrespective of their legal capacity and ability to provide informed consent. As such, anti-doping rule violations and the strict liability standard apply to both minor and adult athletes. Under the current Code, minors are defined as any athlete under the age of 18, and so, their vulnerable status may not be fully considered. Participation in sport (including doping control testing) is a unilateral choice – an athlete can accept or refuse to abide by the Code – if refused, the right to compete is forfeited. This article aims to explore the need for further clarification on the new categorisation of 'mature minor' elite athletes in the Code. We begin by providing an overview of current doping control testing procedures and the specific issues regarding consent to sample collection under the Code's strict liability approach with its associated sanctions. We then examine the rights of minors under the Code within the broader international legal context. We conclude with a reflection on how the notion of mature minor has been addressed elsewhere, and how this can further inform ongoing revisions of the Code. These include greater flexibility in the recognition of both contextual and certain statutory criteria.